Encephalopathy in an adult with cat-scratch disease. (5th March 2018) - Samarkos, Michael; Antoniadou, Vasiliki; Vaiopoulos, Aristeidis G; Psichogiou, Mina
Abstract : We report the case of a 53-year-old healthy man, presenting with confusion. The patient had been clinically diagnosed with cat-scratch disease (CSD) and prescribed a 10-day course of doxycycline orally. Approximately a week after he had completed the treatment, he was admitted to our department with confusion. Neurological examination revealed expressive dysphasia with no motor or sensory deficits. Cerebrospinal fluid (CSF) examination showed only increased content. Imaging with CT and MRI of the brain did not reveal any abnormalities, and funduscopy was normal. Serology confirmed Bartonella henselae infection. CSD-associated encephalopathy was confirmed based on the clinical manifestations, CSF findings and positive serology. The patient was treated with a combination of doxycycline and rifampin and he rapidly improved with complete neurological recovery within 7 days. Encephalopathy is an unusual manifestation of CSD in adults with excellent prognosis.